On a variant of the asymptotic procedure (II: Weakly nonlinear non-autonomous systems) - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2004)
A variant of the asymptotic method is proposed to construct steady solution of weakly nonlinear non-autonomous oscillating systems. The amplitude and the diphase angle of order \(ε^0\) are used as variables, the uniqueness of the asymptotic expansions is assured by stationarity conditions.